Resolution Of Household Conflicts Due To Different Choices Of Presidential Candidates Perspective Of Islamic Law - Siti Mardiyah; Hamda Sulfinadia; Abdurrahman Raden Aji Haqqi (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
Islam indeed requires wives to be obedient to their husbands. However, is this obedience absolute, such that all decisions and commands of the husband must be followed by the wife, including in choosing a presidential candidate? Meanwhile, the state guarantees the right to vote and be elected for all citizens, and any form of restriction constitutes a violation of human rights. This study can provide both theoretical and practical benefits, especially in the context of conflict management and preventing domestic violence arising from differences in political views. This is a qualitative study employing a descriptive analysis approach in the context of a case study. The research predominantly uses secondary data sources obtained from published scholarly works relevant to this study. Data analysis was conducted by gathering information from various secondary literature sources such as journals, articles, and other academic works related to the topic discussed. The data was then analyzed by compiling an initial description from the collected data, followed by further analysis to answer the research questions. The findings of this study conclude that the obligation of a wife’s obedience to her husband is not absolute. Similarly, in determining a presidential candidate, the wife may vote according to her conscience. A wife will not be classified as disobedient or rebellious to her husband solely because of differing political preferences. If household conflicts arise due to differences in presidential candidate preferences, solutions include open communication, setting privacy boundaries regarding politics, not easily believing hoaxes, and reminding each other that household harmony is more important than politics.